Determining Optimal Conditions for Electrochemical Conversion of Phase Flows Under Isotope Exchange; Russian Physics Journal; Vol. 65, iss. 4 - Dorofeeva (Dorofeyeva) L. I. Liudmila Ivanovna (2022, 2022)
Title screen